Total Artificial Heart Salvage of a Heterotopic Heart Transplant Patient. Issue 1 (January 2020) - Gregoric, Igor D.; Akay, M. Hakan; Salas de Armas, Ismael A.; Patel, Manish K.; Nathan, Sriram S.; Akkanti, Bindu; Stojanovic, Stevan; Radovancevic, Rajko; Kar, Biswajit
Abstract : Rescuing heterotopic heart transplantation (HHT) patients remains a challenge in the field. When a 41-year-old patient was transferred to our service, we chose a novel approach that is reported herein. The HHT had been performed over 20 years ago, and in 2016, because of complications, the patient was listed for transplant with a 1A status. For the first time, the SynCardia 50cc total artificial heart (TAH) (SynCardia Systems, LLC, Tucson, AZ) was used in an HHT patient. Investigators attained approval to use the SynCardia 50cc investigational device, as this was an emergent case with few options. The donor heart from the HHT was left in place, alongside the TAH. By leaving the donor heart from the HHT, the need for long and tedious extensive dissection around the right lung was eliminated; thereby reducing the potential risk of lung parenchymal injury, massive bleeding, and complex air leaks. The procedure was successful, and the patient underwent a successful orthotopic heart transplantation six months after being placed on TAH. Abstract : Supplemental Digital Content is available in the text.